The Role of Local Banks in Financing Startups and Their Impact on Economic Development: An Analytical Study - tahar baadache; lakhder abirat (Journal of Excellence for Economics and Management Research, 2025)
Startups play a pivotal role in stimulating innovation, creating job opportunities, enhancing competitiveness, and achieving comprehensive growth. These roles necessitate highlighting their fundamental characteristics and essential requirements for success. Furthermore, the article elucidates the dimensions of economic development and the integral relationship between them and these enterprises, with reference to the trajectory of startup development in Algeria and the efforts exerted to support them. Regarding financing, an analysis was conducted on the overall banking financing provided by local banks, and the contribution of both public and private banks in funding startups, while emphasizing the disparity in financing patterns, where public bank financing is predominantly characterized by fluctuation, whereas private bank financing is marked by gradual growth.